Antioxidant and neuroprotective effects of gossypitrin, a flavonoid from Talipariti elatum, against chemical hypoxia-induced PC12 cell death - María A. Bécquer-Viart; José González-Yaque; Luis A. Fonseca-Fonseca; Yanier Núñez-Figueredo; Gilberto L. Pardo Andreu (GarVal Editorial Ltda., 2018)
Context: Some flavonoids have been described as neuroprotectors. Gossypitrin (Gos) is a natural occurring flavonoid and the main bioactive substance from the flowers of Talipariti elatum Sw. (Majagua azul), traditionally used in Cuba as expectorant and antiasthmatic. Only few reports have documented its antioxidant properties. Aims: To evaluate the antioxidant and cytoprotective effects of Gos against cyanide-induced oxidative stress and cell death in PC12 cells. Methods: Gos effects on DPPH/ ABTS radical scavenging, ferric reducing power and lipid peroxidation were examined. The ischemia/reperfusion neuronal damage was produced by exposing PC12 cells to KCN in glucose-free medium. Gos was added to the incubation medium 30 min before chemical hypoxia induction. The neuroprotective potential of Gos was assessed by measuring cell viability by the MTT assay, the antioxidant enzymes SOD and CAT, and GSH and lipid peroxidation levels. Rutin (Rut), the well-known antioxidant, was used as a reference compound. Results: Gos showed a potent intrinsic antioxidant capacity evidenced by low IC50 and EC50 values for DPPH/ABTS/malondialdehyde and ferric reducing power, respectively. Pre-treatment of PC12 cells with Gos, significantly increased their survival against KCN, restored the levels of GSH and the SOD and CAT enzymes activities, as well as reduced the level of lipid peroxidation. Its antioxidant effects were higher than those elicited by Rut. Conclusions: The results show for the first time the neuroprotective potential of Gos against hypoxic cell damage, probably associated to its antioxidant effects.